Investigation of nonequilibrium in plasma of ARC discharge between melting electrodes - Fesenko, S.O.; Kleshich, M.M.; Veklich, A.N. (Вопросы атомной науки и техники, 2018)
In this paper, the different scenarios of experimental data treatment are considered, which may lead to contrary conclusions about the possibility of realization of a local thermodynamic equilibrium in the plasma. In particular, the level of detail of the plasma components of free-burning in air electric arc (in particular, account of molecule of nitric oxide) have an effect on the region of nonequilibrium in the discharge plasma at arc current of 3.5A.